The Application of choice of law and choice of forum clauses to Islamic banking and Financial Cross Border Transactions - Hasan, Aznan; Win, Kyaw Hla (AENSI Publications, 2012)
Litigations in cross border transactions are inevitable. There would be legal uncertainty and ambiguity without identifying the governing law and the appropriate forum for settling disputes arise from the cross border transactions. Accordingly, the application of both choice of law and choice of forum clauses are vital in Islamic banking and financial cross border transactions. This paper, therefore, intends predominantly to analyze critically the application of these two clauses to Islamic banking and financial cross border transactions. Repeatedly, parties involved in such transactions used to refer a foreign law as a governing law and Shari'ah as a general referral to the contract. There were cases where courts refused to apply Shari'ah principles to the disputes and decided even contrary to it based on the ground that it is not a law of a country rather being general principles. In order to address this issue it is suggested that there should be a comprehensive and efficient international standardize set of rules which govern Islamic banking and financial products; and ample of forums to adjudicate disputes resulting from Islamic banking and financial cross border transactions in line with the Shari'ah. If these were facilitated, it is advisable to the parties to choose that international Shari'ah standard as the governing law of the contract and select one of the Islamic banking arbitration centers as the venue to resolve disputes in the spirit of Shari'ah.